Learning the critical success factors in the production of a mechanical system such as the 76mm armoured vehicle (Rooikat) - De Jager, Nico (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Ing.) -- University of Stellenbosch, 1992.